Trading by professional traders: An experiment - Marco Cipriani; Roberta De Filippis; Antonio Guarino; Ryan Kendall (Federal Reserve Bank of New York, 2020)
We examine how professional traders behave in two financial market experiments; we contrast professional traders' behavior to that of undergraduate students, the typical experimental subject pool. In our first experiment, both sets of participants trade an asset over multiple periods after receiving private information about its value. Second, participants play the Guessing Game. Finally, they play a novel, individual-level version of the Guessing Game and we collect data on their cognitive abilities, risk preferences, and confidence levels. We find three differences between traders and students: Traders do not generate the price bubbles observed in previous studies with student subjects; traders aggregate private information better; and traders show higher levels of strategic sophistication in the Guessing Game. Rather than reflecting differences in cognitive abilities or other individual characteristics, these results point to the impact of traders' on-the-job learning and traders' beliefs about their peers' strategic sophistication.
Keywords: C93; G11; G14; 330; bubbles; experiments; financial markets; information aggregation; professional traders; strategic sophistication